Main differences between distance and sprint world-class cross-country skiers - Fabre, N.; Bortolan, L.; Pellegrini, B.; Schena, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The best predictors of a cross-country skiing sprint performance have already been studied (1,2). However and to our knowledge, specialists of sprint and distance races have never been compared. The purpose of this study was to determine the main physiological and biomechanical differences between distance and sprint cross-country skiers. Methods: Ten elite male skiers from the national Italian ski team [6 from the world-cup distance group (D) and 4 from the world-cup sprint group (S)] were evaluated on the basis of a roller-skiing test on treadmill using the double poling technique. The start speed was fixed at 10 km/h and increased by 0.5 km/h every 30-sec work period until exhaustion with a constant inclination of 6%. Oxygen uptake was continuously measured. Biomechanical data [maximal poling frequency and maximal poling force (Fmax)] were obtained using load cells inserted under the poles handgrips. The total power output was calculated across each speed as the power required to overcome rolling resistance and to lift the body against gravity. Results: Body-weight (BW) and Fmax were significantly higher (P<0.05) for the group S (78.5±5.8 kg and 156.0±9.8 N, respectively) compared to the group D (70.0±5.0 kg and 136.4±13.7 N, respectively). S and D groups did not significantly differ in peak oxygen uptake (4.4±0.4 L/min and 4.8±0.4 L/min, respectively), maximal power (328.4±21.2 W and 330.1±25.7 W, respectively), maximal poling frequency (63.9±4.4 cycles/min and 68.0±5.9 cycles/min, respectively) and Fmax/BW (2.0±0.1 N/kg and 2.0±0.1 N/kg, respectively). When peak oxygen uptake (VO2peak) and maximal power (Pmax) were expressed relatively to BW, values of the S group (56.3±4.3 mL/min/kg and 4.2±0.3 W/kg, respectively) were significantly lower (P<0.01) than the values of the D group (70.8±2.9 mL/min/kg and 4.7±0.1 W/kg, respectively). Finally, among the parameters measured during this test, Fmax appeared as the best predictor (irrespective to the S or D group) of sprint racing performance (estimated by means of the specific sprint International Ski Federation ranking). The correlation showed that 70% of the variability of the performance in sprint races could be explained by absolute Fmax (r2=0.70). Discussion: The higher BW and Fmax appeared to be the main different parameters (among those measured with this kind of test) between a sprint and a distance specialist in cross-country skiing. Moreover, BW-to-power (aerobic and mechanical) ratio was optimized in distance skiers. Expressed in absolute value, no difference was observed in VO2peak between sprint and distance skiers. Thus, as suggested by Stogll T. et al., the sprint performance seems to be mainly dependent of muscular factors but a high aerobic capacity is a prerequisite.